Etika Perkotaan - Ali Romdhoni (Jurnal Bimas Islam, 2017)
The imagination city of Indonesian society is believed to give a better life. The word 'city' has also become a symbol of the ideal conditions in people’s lives. The person who has succeeded in becoming a city is called a successful person, his social status is also considered higher. Finally, there are many people who want to move to the city. On the other hand, the city has also eliminated the noble values, knowledge and culture of the Indonesian nation. Tolerance, courtesy, care and wisdom in the village have been lost in the city. Urban environment has killed the personality of Indonesian society. This paper wants to offer the values that must be considered in building the city, so that the city still provide a sense of comfort and security for the inhabitants. Both children, adults, and parents. Kota dalam imajinasi masyarakat Indonesia diyakini bisa memberi kehidupan yang lebih baik. Kata 'kota' juga telah menjadi simbol atas kondisi yang ideal dalam kehidupan masyarakat. Orang yang telah berhasil menjadi warga kota disebut sebagai orang yang sukses, status sosial-nya juga dianggap lebih tinggi. Akhirnya, ada banyak orang yang ingin berpindah ke kota. Di sisi lain, kota juga telah menghilangkan nilai-nilai luhur, pengetahuan dan budaya bangsa Indonesia. Toleransi, sopan santun, kepedulian dan kebijaksanaan yang ada di desa telah hilang di kota. Lingkungan perkotaan telah membunuh kepribadian masyarakat Indonesia. Penelitian ini ingin menawarkan nilai-nilai yang harus diperhatikan dalam membangun kota, agar kota tetap memberi rasa nyaman dan aman bagi penghuninya. Baik anak-anak, orang dewasa, maupun orang tua.